Advancements in research leveraging phage display technology for gastric cancer diagnosis and treatment - Wang, Zhenyu; Li, Yuping; Lin, Jun; Deng, Fuyu; Liu, Yao; Ji, Yuan (Frontiers in Microbiology, 2025)
Gastric cancer persists as a major global health challenge, ranking among the leading causes of cancer-related deaths worldwide. The high mortality rate primarily stems from difficulties in early detection, often resulting in late-stage diagnosis when treatment options are limited. Phage display technology, developed in 1985, has emerged as a powerful tool in gastric cancer research, facilitating significant advances in three key areas: (1) identification of novel biomarkers for early detection, (2) screening of targeted therapeutic molecules, and (3) development of diagnostic reagents. This comprehensive review examines current applications of phage display in both diagnostic and therapeutic approaches for gastric cancer, while critically analyzing existing limitations in sensitivity, specificity, library diversity, and screening efficiency. Furthermore, we discuss the promising potential of integrating phage display with other cutting-edge technologies, proposing future research directions that could enhance its clinical utility and ultimately improve patient outcomes in gastric cancer management.